PERENCANAAN SALURAN PRIMER, SEKUNDER DAN TERTIER PADA DAERAH IRIGASI SITA - Halimah Masloman (PPLH-SDA, Lembaga Penelitian Unsrat Manado, 2013)
The net needs of water in rice field (NFR) in a special irrigation area. Irrigation Sita Region particularly is very important, because by this bearer of channel, the water from intake building can be irrigated to all sector of rice field. That is why the main goal of an irrigation network can be reached. In a plan of an irrigation network system, especially bearer channel planning should be planned as well, so it can drain a maximum debit, one of its technical consideration is the economic diagonal display design by optimalizing hydrolyc’s radius and also minimalizing net cycling. Planning of primer, secondary and tertier channels with the economic diagonal display should be based on existing situation in the field followed by hydrolyca and also hydrology analysis. Hydrology analyse is consist of the net needs of water in rice field (NFR) debit plan (Q) and then hydrolyca analyse such as channel dimension design and heigt surface water which is needed. Based on analysis result, can be obtained the net needs of water in rice filed (NFR) as much as 1,204 lt/de/ha. Maximum debit for primer channel is 0,786 m3/det, while secondary channel is 0,688 m3/det and for tertier channel is 0,159 m3/det. Planning result of primer channel dimension is trapezium formed, with its basic wide of channel (Bb) 0,9 m, current dept (h) is 0,8m and on the other hand primer channel dimension is also in the form of four sided, with its basic wide channel (B) is 1,5 m, current depth (h) is 0,7 m. while trapezium form is for secondary channel dimension with its channel basic wide (Bb) 0,7m, current depth (h) is 0,6 m and secondary channel dimension is also four sided form with its channel basic wide (B) 1,2m, current depth (h) is 0,6m. For tertier channel is in the form of trapezium with its channel basic wide (Bb) 0,4m, current depth (h) is 0,5m and furthermore, this channel is also four sided form with its basic wide of channel (B) is 1,0m while for its current depth (h) is 0,5m.